Relation of religion and practical politics: Contextual adoption of constitutional Islamic jurisprudence for Muslim clerics in Indonesia - Imam Yahya; Sahidin Sahidin (HTS Teologiese Studies/Theological Studies, 2022)
Some clerics (ulama) in the Islamic world are of the view that practical politics is closely related to Islam, which regulates how an order of state is run. This view historically departs from Islamic constitutional jurisprudence texts that justify political Islam. Likewise, some Islamic boarding schools’ (pesantren) clerics, better known as kyai in Indonesia, are of the view that practical politics is not only a world affair but also an activity based on the application of Islamic legal principles in achieving public welfare. This study aims to determine the academic basis of pesantren ulama in making decisions to be active in practical politics in Indonesia. Using a qualitative approach through interviews, the results of this study indicate that the political decisions of pesantren ulama are strictly based on the perspective of political Islam and fiqh principles that justify the involvement of ulama in politics. Furthermore, the conclusion leads to three perspectives in political motivations for pesantren’s ulama: to gain power, to preach Islamic values, and to demonstrate the existence of ulama in modern state administration.